Analysis On Effect Of Antenatal Care Towards Prevention Labor Complications Among Mothers, Central Lampung - Indayani, Ninik; Fijri, Bayu (Akademi Kebidanan Bunga Husada Samarinda, 2021)
Introduction: Maternal mortality rate is one indicator to view the health status of women. This indicator is not only able to assess maternal health programs, moreover, is able to assess the degree of public health, because of it’s sensitivity to the improvement of health services, both in terms of accessibility and quality. Based on the Health Profile of Lampung in 2014 the maternal mortality rate in the province of Lampung increased from 2007 by 228 to 359 every 100.000 live births in 2012. As for the causes of maternal deaths in the province of Lampung in 2013 caused by as many as 47 cases (2.14%) of hemorrhage, eclampsia as 46 cases (2.08%), 9 cases (0.4 %)of infection, obstructed labor 1 case (0.04%), 1 case (0.04%) of abortion and others as many as 54 cases (2.45%).Objectives: To determine the relationship between antenatal care and labor complication at health clinic, Central Lampung. Study Design: The study design used is crossectional research design. In this study will explore the relationship between implementation antenatal care with labor complications. The reason for the use of this design is a researcher wants to observed phenomena at a certain point of time. Data colletion: Instrumen in this study using the chek list to collect the data. The chek list indicators contains data that contains 10 standard pregnancy care services. The chek list is expected to be able to monitor whether mother are always checkups in accordance with the standard of care a pregnancy or not.Data Analysis: To analyze the normality data using the spss computer programme. Normality test is used to determine whether the data were analized normal distribution or not. If normal used chi square and if an normal used product moment test.Univariate analize In this study used frequence distribution to analyze independet variable and dependent variable. Bivariate analyze is used chi aquare test to identify the relationship between antenatal care with complication of the labor. Results: there is 86 mothers are 52% (45 mothers) getting a in adequate antenatal care and 48% (mother) gettting antenatal adequate. The maternal frequency distribution with labor complication was 23% (20 mothers). While mothers who did not experience labor complications of 77% (66 mothers) of 86 respondents. While the results of Chi Square (X2) test obtained Fisher'r Exact Test value of 0.029 kurang dari α 0.05, which means there is a significant relationship between maternal ANC with the incidence of labor complications. Conclusion: The government should continue to improve health programs, especially regarding the program in order to reduce the number of maternal complications that occur in the mother. In addition, the government continues to mobilize health workers and the community to play an active role in efforts to reduce and prevent the occurrence of birth complications such as maternity classes and counseling. It is no less important that the government should increase guidance to cadres and health workers to conduct counseling and promotive efforts for in order to prevent birth complications.